2003
DOI: 10.1002/jmri.10303
|View full text |Cite
|
Sign up to set email alerts
|

Rapid hyperpolarized 3He diffusion MRI of healthy and emphysematous human lungs using an optimized interleaved‐spiral pulse sequence

Abstract: Purpose: To develop and validate an interleaved-spiral diffusion pulse sequence capable of hyperpolarized 3 He MR imaging of the whole lung in less than 10 seconds. Materials and Methods:Hyperpolarized 3 He diffusion measurements were performed in seven healthy volunteers and five patients with emphysema using an interleavedspiral pulse sequence that provided 11 contiguous 15-mm thick coronal ADC maps, with an in-plane resolution of 3.9 mm, covering the whole lung in 5.5 seconds. The resulting means and SDs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 14 publications
1
39
0
Order By: Relevance
“…The function g(r / R) can be well approximated by the following expression, shown as the solid line in Figure 7b: (14) Combining Eqs. (13)- (14), the parameter β L can be related to the geometrical parameters of the model as follows: (15) …”
Section: Longitudinal Diffusivitymentioning
confidence: 99%
“…The function g(r / R) can be well approximated by the following expression, shown as the solid line in Figure 7b: (14) Combining Eqs. (13)- (14), the parameter β L can be related to the geometrical parameters of the model as follows: (15) …”
Section: Longitudinal Diffusivitymentioning
confidence: 99%
“…ADC measurements are, therefore, a measure that is altered by changes in the lung microstructure and give information about changes in function. ADC appears to be a sensitive (76) and reproducible (67) marker for early detection (25,76) and progression (75) of disease and other processes affecting the size of alveoli and small airways (92).…”
Section: Helium Diffusion As a Measure Of Lung Microstructurementioning
confidence: 99%
“…Hyperpolarized 3 He MR has also been used to evaluate the ADC and thus estimate peripheral air space size in normal subjects of different ages and patients with emphysema. The ADC is increased with increasing age (24), is larger in active and passive smokers than in healthy neversmokers (25), and is larger in patients with emphysema (25,76). Thus this technique may provide insights into early diagnosis of airway disease or response to treatment.…”
Section: Helium Diffusion As a Measure Of Lung Microstructurementioning
confidence: 99%
“…Previous studies of human and animal lungs have demonstrated the utility of hyperpolarized 3 He magnetic resonance lung imaging techniques and have proven particularly effective at detecting and tracking ventilation defects. These techniques can, therefore, be extremely useful in studying diseases of the lung that are characterized by such defects (1)(2)(3)(4)(5)(6)(7). In addition, in vivo measurements of the 3 He apparent diffusion coefficient (ADC) in emphysema have effectively quantified lung structure by measuring its restrictive effects on the motion of 3 He gas atoms (1), providing detection and longitudinal tracking of changes in microarchitecture resulting from disease destruction of alveolar walls.…”
mentioning
confidence: 99%
“…In addition, in vivo measurements of the 3 He apparent diffusion coefficient (ADC) in emphysema have effectively quantified lung structure by measuring its restrictive effects on the motion of 3 He gas atoms (1), providing detection and longitudinal tracking of changes in microarchitecture resulting from disease destruction of alveolar walls. HP 3 He lung MRI studies of emphysema in humans (1)(2)(3)(4)(5) and a variety of animals, including pigs, dogs, guinea pigs, and rats, have produced very promising results (6 -10). However, no applications of hyperpolarized 3 He magnetic resonance imaging to the mouse have been reported.…”
mentioning
confidence: 99%